1987
DOI: 10.1107/s0108270187091509
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of atomic thermal parameters of lead chalcogenides, PbS, PbSe and PbTe

Abstract: Thermal parameters of PbX (X = S, Se and Te) have been measured at temperatures ranging from 120 to 298K by single-crystal X-ray diffraction methods. Crystal data: Mr= 239.25, 286.15, 334.79; cubic; Fm3m; Z=4; MOKal; 2=0.70926A; a=

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
67
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(83 citation statements)
references
References 6 publications
16
67
0
Order By: Relevance
“…Under standard conditions, the experimentally known modification of lead sulfide crystallizes in the NaCl structure type (B1) [31]. PbS undergoes a pressure-induced phase transition from the NaCl (B1) type to an intermediate orthorhombic phase (suggested to belong to the B16 or B33 structure types at 2.2 GPa [32][33][34].…”
Section: Lead Sulfide (Pbs)mentioning
confidence: 99%
“…Under standard conditions, the experimentally known modification of lead sulfide crystallizes in the NaCl structure type (B1) [31]. PbS undergoes a pressure-induced phase transition from the NaCl (B1) type to an intermediate orthorhombic phase (suggested to belong to the B16 or B33 structure types at 2.2 GPa [32][33][34].…”
Section: Lead Sulfide (Pbs)mentioning
confidence: 99%
“…At high temperatures (450 C and 500 C), the alloys between the PbTe and AgSbTe 2 phases form a complete solid solution; the critical temperature for the miscibility gap should be located between 400 C and 450 C. The formation of the complete solid solution is possible because the crystal structures of PbTe and AgSbTe 2 belong to the same space group, Fm 3m (NaCl-type structure, see ref. 41 for PbTe and ref. 42 for AgSbTe 2 ‡).…”
Section: 34mentioning
confidence: 99%
“…Under normal conditions, PbS is a semiconductor with a cubic B1 structure [8,9]. Recent studies have shown that the crystal structure of the PbS nanofilms (thin nanostructured films) may be different.…”
Section: Introductionmentioning
confidence: 99%